Наукові аспекти вирішення проблеми йододефіциту населення України - Tronko, M.D.; Olumbryk, M.O.; Kravchenko, V.I.; Balyon, Ya.G. (Ендокринологія | Endokrynologia, 2011)
Наукові аспекти вирішення проблеми йододефіциту населення України